RANCANGAN SISTEM MONITORING DAN KENDALI SUHU REAKTOR DI LABORATORIUM - Vendamawan, Rico (METANA, 2012)
Proportional control system design, hardware in the form of temperature control systems using Wifi, to control the Reactor heater on Laboratory of Diploma Chemical Engineering. In this system made the system interface and device temperature control system for reading the same data records with the reading of stored data and graphical visualization using Borland Delphi. To maintain a stable temperature of the reactor need to be made primarily on monitoring and temperature control systems that work online using Wifi, the result is that the actual temperature control system and can monitor the temperature of it online. This study uses a temperature sensor type LM 35 which is a type of semiconductor that has an integrated signal conditioning part of it. Using the internal ADC 10 bits of mikrokontrol AVR ATmega 8535, as an interface. To perform wireless data communications that have used Wifi 802.11g specification. Wifi injected data from a computer using a standard protocol TCP / IP. By doing a set of IP addresses allows the data on a computer can be accessed by another computer around it. Validation test was done by comparing the temperature readings by the sensor LM35 with Thermo standard test equipment 300, the test results obtained device temperature control system that can work in accordance with the principles of control on the basis of proportional control theory, with errors less than 2%. Keywords: temperature control, proportional control, Wifi